Oxygen uptake is more efficient in idiopathic pulmonary arterial hypertension than in chronic thromboembolic pulmonary hypertension. Issue 1 (22nd September 2015) - Shi, Xiaofang; Guo, Jian; Gong, Sugang; Sapkota, Rikesh; Yang, Wenlan; Liu, Hui; Xiang, Wenjing; Wang, Lan; Sun, Xingguo; Liu, Jinming
Abstract: Background and objective: The responses of oxygen uptake efficiency (OUE) during cardiopulmonary exercise training (CPET) have not been reported in patients with pulmonary hypertension. We aimed to investigate the differences in OUE between patients with idiopathic pulmonary arterial hypertension (IPAH) and chronic thromboembolic pulmonary hypertension (CTEPH). Methods: Forty‐four patients with IPAH and 29 patients with CTEPH were retrospectively enrolled into our study. All patients underwent right‐heart catheterization, pulmonary function test and performed the 6‐min walk test and CPET. Results: We found that oxygen uptake efficiency plateau (OUEP) and oxygen uptake efficiency at anaerobic threshold (OUE@AT) was significantly higher in IPAH than that in CTEPH (both P  = 0.002). However, patients with CTEPH had lower mean pulmonary artery pressure, pulmonary vascular resistance and transpulmonary gradient (all P  < 0.05). The correlation between OUEP and heart rate at anaerobic threshold (HR_AT) was significant (r = 0.376, P < 0.05); however, no statistically significant correlation was found with ventilation at anaerobic threshold (VE_AT) (r = −0.074, P > 0.05) in patients with IPAH. In patients with CTEPH, both anaerobic threshold (r = 0.307, P  > 0.05) and VE_AT (r = −0.709, P  < 0.0001) were reduced. OUEP were higher in WHO functional class I/II patients than in WHO functional class III/IV patients (all P  < 0.05). Conclusions: OUEP and OUE@AT are higher in IPAH than that in CTEPH not in proportion to haemodynamics, probably due to differences in cardiac function and pulmonary vascular occlusion. OUEP correlates well with the exercise capacity and the severity of the disease. Abstract : Responses of oxygen uptake efficiency during cardiopulmonary exercise testing in patients with pulmonary hypertension are reported. We observed a higher oxygen uptake efficiency in patients with idiopathic pulmonary arterial hypertension compared to patients with chronic thromboembolic pulmonary hypertension. The oxygen uptake efficiency plateau correlates with exercise capacity and disease severity.